Secondary school students' misconceptions in genetics: origins and solutions - Machová, Markéta; Ehler, Edvard (Journal of biological education, 2023)
Even though genetics has been implemented in biology curricula at secondary schools for decades, reports repeatedly indicate that students still hold various misconceptions about this topic. To successfully target these misconceptions, we need to know their nature and origin. We aimed to investigate these properties in the Czech educational system among students of lower-secondary education (ISCED 2) and upper secondary education (ISCED 3). Students underwent a test focused on the basic concepts of genetics based on the content of the national curriculum and current textbooks. The results showed that students have general ideas about the nature of genetic information but struggle to synthetise this knowledge into a deeper understanding of functions in the living body. In many cases, these findings resulted in an increase of various misconceptions. Compared with data about the Czech educational environment and its properties, these problems are caused by a disconnection between the rules of inheritance and functions and impacts of DNA (trait development) on multiple levels of biological organisation both in the national curriculum and textbooks. Therefore, in order to prevent misconceptions, we should focus not only on the way lesson are conducted but also on the changes of national educational policies in the Czech Republic.